Konsep Istikhlaf Ekonomi Islam dalam Pandangan Yusuf Qardawi - Nurizal Ismail; Siti Aisyah (Tathawwur: Jurnal Ekonomi Pembangunan dan Keuangan Islam, 2024)
Islamic economics provides a unique perspective on wealth administration, distinct from Capitalism and Socialism. A key concept in Islamic economics is “istikhlaf,” which asserts that wealth belongs to Allah (God), and human are merely its trustees. The aim of this research is to explore the concept of istikhlaf in Islamic economic activities through the views of Yusuf Qardawi, a Muslim scholar who has also shown considerable interest in Islamic economics through his works. The research method used in this study is qualitative inductive with a literature study, examining primary sources from Yusuf Qardawi’s work titled “Ethics and Norms in Islamic Economics,” and secondary sources from articles and books related to the topic. Thematic analysis was employed to reduce, classify, and analyze data across three economic activities: production, consumption, and distribution. The result indicates that istikhlaf has a positive impact on economic activities such as production, consumption, and distribution. In production, istikhlaf encourages the wise and responsible use of resources. Consumption should be carried out frugally in accordance with Shari’ah, avoiding wastefulness, and greed. The distribution of wealth must be fair and equitable, avoiding arrogance, exploitation, and injustice. This research contributes to the understanding that the concept of istikhlaf in economic activities focuses not only on worldly aspects but also on the hereafter, through individual, social, and environmental responsibilities for sustainable development.